A case report involving the experience of pervasive pregnancy denial: detailed observation of the first 12 postpartum weeks - Natalia Chechko; Elena Losse; Susanne Stickel (BMC Psychiatry, 2022)
Abstract Background Pervasive pregnancy denial is a rare condition associated with distress and unassisted delivery. Case presentation The case involves a 38-year-old woman (NN), with two older children (ages 8 and 11), who was unaware, until delivery, that she had been pregnant. The case is discussed in the context of a 12-week observation of postpartum mood, stress, and mother-child attachment. NN and other 558 non-depressed women (mean age 32.41 years) were selected from the pool of participants in the RIPOD (risk of postpartum depression) study. All participants were recruited within 1–6 days of delivery. In addition to surveying depressed mood at childbirth, remote assessments of mood, mother-child attachment, and perceived stress were conducted at 3, 6, 9, and 12 weeks postpartum. Every other day, the participants also reported their current perceived stress levels based on a scale from 1 (low) to 10 (high). During the entire period of postpartum observation, NN reported no symptoms on the Edinburgh Postpartum Depression Scale, similar to only 1.6% of the sample, no stress as 0.7% of the sample, and above-average mother-infant bonding akin to only 4.6% of the sample. Her daily stress levels showed no disturbance, which was the case for only 3.32% of the total sample. On the day of delivery, NN reported a stress level of 1 (the minimum possible level), which was reported by only 4.2% of the total sample. However, NN reported the experience of delivery to be traumatic given that the child had fallen to the floor. Conclusion The experience of a denied pregnancy did not appear to disturb NN at any time point, not even on the day of delivery. Compared to NN, the other non-depressed participants reported wide fluctuations in stress levels during the observation period. NN did not report any risk factors for denied pregnancy. Thus, she belonged neither to any group of typical pregnancy deniers, as reported in the literature, nor to a typical postpartum group. We postulate, therefore, that the extent to which pregnancy denial can be deemed a normal variation, unrelated to a psychological or physiological condition, depends largely on personal traits.